Alternative hypotheses for mammalian herbivore preference of burned areas in a savannah ecosystem. (21st May 2016) - Eby, Stephanie; Ritchie, Mark E.
Abstract: Mammalian herbivores prefer burned areas and this attraction has largely been attributed to the increased nutrient content of the postfire green flush and more recently to the avoidance of predators. However, alternative reasons for this attraction could be: (i) to avoid disease carrying and behaviour changing invertebrates; (ii) because burned areas are warmer microclimates; or (iii) to obtain minerals from the ash. This study tests for differences in tick and fly (Diptera) numbers between burned and unburned areas in Serengeti National Park, Tanzania. It also tests for differences in ground and air column temperatures between burned and unburned areas and for differences in the mineral content of ash in burned areas compared to the mineral content of green leaves in unburned areas. We found no difference in the abundance of either type of invertebrate between burned and unburned areas. Only ground temperature was higher in burned areas and this was only during the middle of the day, when increases in temperature would be less important than at night. Ash was higher in Al, Ca, Cu, Mg, Mn and P than nearby green leaves from unburned vegetation. Thus, obtaining minerals from ash is the only alternative reason for attraction to burned areas that maybe supported by this study.